Intramural pregnancy: a diagnostic dilemma for an obstetrician - khandasu, Seema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Intramural ectopic pregnancy is one of the rarest types of ectopic pregnancy,with risk of 1:30000.Confirmation of intramural ectopic pregnancy is difficult and is often performed intraoperatively.Intramural ectopic pregnancy often requires hysterectomy to avoid life-threatening haemorrhage.We present a case of intramural ectopic pregnancy in the second trimester.Transvaginal ultrasound and MRI are important non-invasive methods in diagnosing this type of ectopic pregnancy.Clinicians should provide consideration to a combination of strategies and do their best to preserve patient’s ”uteri and fertility”.